Trichodinid ciliates (Peritrichia: Trichodinidae) from the Bay of Kiel, with description of Trichodina claviformis sp. n. - Dobberstein, Reimer C.; Palm, Harry W. (Institute of Parasitology, České Budějovice, Czech Republic, 2000)
Investigations on the epizoic fauna of Gadus morhua (L.), Platichthys flesus (L.) and Oncorhynchus mykiss (Walbaum) from the Kiel Fjord and Kiel Bight were carried out from September 1996 to March 1997. Smears from 120 G. morhua and 92 P. flesus caught using fish traps and trammel nets, and of 35 O. mykiss obtained from a local fish farm in the Kiel Fjord revealed the presence of three species of trichodinid ciliates, Trichodina claviformiis sp. n., Trichodina jadranica Haider, 1964 and Trichodina raabei Lom, 1962. The new species can be distinguished from other trichodinids by its large size in combination with the characteristically shaped adhesive disc containing denticles with club-like formed thorns. The thorns are directed anteriorly and not towards the centre of the adhesive disc. As the Kiel Bight and Kiel Fjord are new locality records for T. jadranica and T. raabei, morphological data are provided for both species. Trichodina claviformis is the first record of a peritrichous mobiline ciliate from Atlantic cod of the Baltic Sea. An identification key for 16 Trichodina species occurring on Baltic Sea fishes is provided based on the morphology of the adhesive disc and other well-established features. The occurrence of trichodinid ciliates on G. morhua and P. flesus in the Baltic Sea is discussed, especially considering the biology of the host and a possible host specificity of the species.